Maternal and perinatal outcome in hypothyroidism in pregnancy: a prospective observational study - Sharma, Deepika; Dixit, Pratibha V.; Gavit, Yogita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: This study was conducted to analyse the antenatal complications, perinatal outcome and to be advocate routine screening for thyroid disorders in pregnancy. This study was prospective and observational study with 50 cases which was newly diagnosed when suspected as pregnancy with thyroid disorders. The commonest thyroid disorder found in pregnancy is hypothyroidism and it adversely affects the maternal and fetal health in the form of infertility, early pregnancy loss, PIH, anaemia, IUGR, PROM, preterm labor, neonatal and maternal morbidity and mortality. If thyroid disorders are appropriately detected and treated either before or in early pregnancy, the adverse maternal and fetal outcome can be prevented. Methods: The present study was conducted in a tertiary care centre Mumbai from June 2015 to October 2016. All pregnant females who are newly diagnosed as hypothyroid, attending the ANC clinic were enrolled in the study. Results: In the present study, most common obstetric complication observed was preeclampsia and most common fetal complication was preterm delivery. Conclusions: In view of the high prevalence of thyroid dysfunctions in Indian pregnant woman and its association with different adverse pregnancy related complications we recommend routine screening for thyroid dysfunctions in pregnancy.